FATHERING STYLES OF MUSLIM FAMILIES PERCEIVED FROM PERSONALITY TYPES IN NORTH SUMATERA - Nurhayani Nurhayani (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2019)
Fathering styles are highly influenced by the cultural background from which the father are raised. These styles will be observed by children and eventually become an imitated model for children in shaping their attitude and behaviour as well as their ethnic identity representing their cultural values. The objectives of this research are to know the difference of fathering styles between fathers in Minangkabau families and Batak families perceived from their personality types. The subjects of this research were 90 fathers in Medan, North Sumatera which consist of 45 fathers of Minangkabau ethnicity and 45 fathers of Batak ethnicity. The data of the study were collected by using two scales, which are personality types scale and fathering style scale. Analysis of Variance (ANOVA) was applied to analyze the data. The result of the analysis shows that personality types and ethnicity interact each other in affecting fathering styles (F: 5.872; p = 0.004 < 0.05), so there is a difference of fathering styles between Minangkabau fathers and Batak fathers perceived from introvert and extrovert personality types. A final contribution of this study is the effort to save young generation who live fatherless and support well function families through fathers’ role in transmitting good cultural values of fathers’ ethnicity, so it is suggested that fathers’ involvement should be existed in raising children’s development any condition even divorce can not be avoided. The paternal figure should always be present in children’s lives both my father’s direct involvement and by the involvement of other paternal figures. The good paternal figure will help children to avoid the social problems they face in life Pola pengasuhan ayah tidak terlepas dari latar belakang budaya yang mempengaruhi kepribadian ayah sejak kecil. Pola pengasuhan ayah akan diamati oleh anak dan menjadi model figur yang ditiru anak dalam berperilaku dan menjadi ciri identitas etnik yang mewakili kepribadian sukunya. Penelitian bertujuan untuk mengetahui dan memahami perbedaan pola pengasuhan ayah ditinjau dari tipe kepribadian pada keluarga Batak Muslim dan keluarga Minang. Subjek penelitian adalah 90 orang ayah di Kota Medan, Sumatera Utara yang terdiri 45 orang ayah suku Minang dan 45 orang ayah suku Batak. Pengambilan data menggunakan dua skala, yaitu skala tipe kepribadian dan skala pola asuh ayah. Analisis Varians dua arah (Two Ways ANOVA) digunakan sebagai metode untuk mengalisis data. Hasil analisis data menunjukkan bahwa tipe kepribadian dengan suku saling berinteraksi dalam mempengaruhi pola pengasuhan ayah. Kontribusi penelitian ini adalah untuk menyelamatkan generasi muda yang hidup tanpa ayah dan mendukung keutuhan fungsi keluarga melalui peran ayah dalam mentransmisi nilai budaya yang baik dari sukunya, maka disarankan agar keterlibatan ayah hendaknya diupayakan dalam kondisi apapunBerdasarkan hasil penelitian di atas, disarankan agar keterlibatan ayah dalam pengasuhan anak harus ada dalam kondisi apapun, bahkan saat perceraian tak dapat dihindarkan. Figur ayah tidak boleh hilang dalam kehidupan anak baik itu dengan menghadirkan keterlibatan ayah secara langsung maupun dengan menghadirkan figur lain yang dapat melakukan peran ayah. Figur ayah yang baik akan membantu anak terhindar dari masalah-masalah sosial yang dihadapi dalam kehidupannya